1999
DOI: 10.1177/10547739922158214
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge of Pain Assessment, Pharmacologic and Nonpharmacologic Interventions

Abstract: This study compared differences in knowledge of pain assessment and pharmacologic and nonpharmacologic pain management strategies among 232 L.P.N.s and R.N.s from three hospitals. Twenty-three adult medical, surgical, and special care units were represented. The "Knowledge of Pain Management" tool measured knowledge of pain assessment, drug and nondrug strategies, and was based on AHCPR guidelines. Scores ranged from 24% to 92%. There were significant differences in scores across hospitals and between R.N.s an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
2
18
2
Order By: Relevance
“…It has been proposed that effective pain assessment and pain management competencies must be based on scientific knowledge and research and systematically used in the nursing care of patients. Otherwise, patients might be treated ineffectively for pain, which in turn might lead to an increase in patients' stress and their dissatisfaction with nursing care 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that effective pain assessment and pain management competencies must be based on scientific knowledge and research and systematically used in the nursing care of patients. Otherwise, patients might be treated ineffectively for pain, which in turn might lead to an increase in patients' stress and their dissatisfaction with nursing care 25 …”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, patients might be treated ineffectively for pain, which in turn might lead to an increase in patients' stress and their dissatisfaction with nursing care. 25 What is more, as there is a dearth of research into undergraduate and graduate nurses on their practice, knowledge and attitudes towards pain management in Iran, both qualitative and quantitative inquiry approaches can help nursing educators to evaluate the pain content of the nursing curriculum for its accuracy and currency. This might increase the level of knowledge of effective management of patients' pain, which ultimately might lead to acceptable patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We, and other authors, suggest that non-pharmacologic pain treatment deserves more emphasis in nursing education. 23 Very young children have long been recognized as an at-risk group for under-treatment of pain. [24][25][26] When one is designing a triage-initiated pain protocol, special attention should be drawn to patients aged younger than 2 years, as well as the use of age-appropriate validated pain assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge about pain management has been found among students (11), in a sample of a nursing faculty (12), and among hospital nurses (11, 13–17) and home care nurses (18, 19). Furthermore, studies have shown that district nurses’ preparedness, nursing documentation and knowledge of caring for people with chronic pain conditions seem to be insufficient (8, 20, 21).…”
Section: Introductionmentioning
confidence: 99%